(untitled) (International Journal of Geoscience, Engineering and Technology, 2024)
A case study was conducted in the urban drainage course, focusing on analyzing drainage systems across various locations of the campus of the Federal University of Jequitinhonha and Mucuri Valleys (UFVJM). Through technical visits, critical issues were identified, such as the insufficiency of storm drains and their obstruction or damage in several locations, including the University Restaurant, the Roundabout, the Engineering Laboratory, the Gymnasium, the ICET (Institute of Science, Engineering, and Technology), and the Transportation Building. These deficiencies compromise the efficiency of stormwater runoff, resulting in flooding and erosion, especially in low-altitude areas like the University Restaurant. The study highlighted the need for interventions to maintain and improve drainage infrastructure, proposing solutions to minimize environmental and structural impacts. Such as adding more drainage grates and storm drain inlets, creating permeable areas, and strategically distributing manholes. This would increase drainage capacity and significantly reduce the risk of flooding and erosion.